Body mass in adolescents with chronic pain: observational study. Issue 5 (28th November 2019) - Gauntlett-Gilbert, Jeremy; Bhat, Chandrika; Clinch, Jacqui
Abstract : Objective: In a paediatric chronic pain population, to determine whether higher body mass was associated with poorer functioning, mood or treatment outcome. Design: Cross-sectional study with examination of treatment outcomes. Setting: Tertiary specialist adolescent pain rehabilitation unit. Patients: 355 adolescents with relatively severe non-malignant chronic pain. Interventions: Intensive 3-week pain rehabilitation programme. Main outcome measures: Objective physical measures (walk, sit-to-stand); self-reported functioning and mood Results: Average body mass index (BMI) in the sample was relatively high (24.2 (SD 5.6)) with 20.5% being classified as obese. However, there were no relationships between body mass and objective physical measures, physical or social functioning, depression or anxiety (all p>0.05). There was a small relationship between higher body mass and greater pain-related fear (r=0.17, p<0.01). Treatment improved all variables (p<0.001) apart from pain intensity. There were no relationships between higher body mass and poorer treatment outcome; in fact, patients with higher BMI showed slightly greater decreases in depression (r=0.12, p<0.05) and pain-specific anxiety (r=0.18, p<0.01) during treatment. Conclusions: Higher body mass does not worsen functioning, mood or treatment response in adolescents with disabling chronic pain. Childhood obesity and chronic pain are both stigmatised conditions; clinicians should avoid implying that high body mass alone is a causal factor in the struggles of a young person with chronic pain.